Labor market trends and outcomes: What has changed since the Great Recession? - Erica L. Groshen; Harry J. Holzer (Institute of Labor Economics (IZA), 2021)
We describe trends in wages and labor force participation for the "working class" - whom we define as workers with high school or less education - compared to those with college or more. We compare cyclical peaks over the entire period 1979-2019, with particular focus on the Great Recession (2007-2010) and recovery (2010-2019). We also present results by gender and race. We find real wage growth in the latter period for all workers, but not enough to change the long-term trends of growing inequality and stagnant wages for the less-educated; and we also find that labor force participation continued to decline for the less-educated, even during the recovery. Gaps between whites and blacks also grew while Hispanics and Asians made more progress. We consider various explanations of these findings, and show that the early effects of the 2020-21 pandemic recession that hurt lesseducated workers and those of color more than anyone else.
Keywords: J6; 330; wages; participation; working class; Great Recession; recovery